Numerical integration algorithm of updated homogeneous anisotropic hardening model through finite element framework - Yoon, Seong-Yong; Lee, Shin-Yeong; Barlat, Frédéric (Computer methods in applied mechanics and engineering, 2020)
In this work, an updated version of the homogeneous anisotropic hardening (HAH20) model proposed by Barlat et al. (2020) is implemented into a finite element framework through a stress integration algorithm. To improve the convergence of this model inside the integration algorithm, the algorithmic step sizes of the solution variable increments are controlled by the line-search method. The HAH20 implementation is validated by comparing the simulation results obtained from the finite element analysis with those calculated by stand-alone HAH20 code. In addition, the simulation results of tests, including strain path changes such as tension–compression and cross-loading, are compared with experimental measurements, and the effectiveness of the step size control in the current HAH20 model is investigated. The performance of the implemented algorithm is analyzed through convergence maps for critical strain path change simulations.